PENGARUH LATAR BELAKANG KEHIDUPAN TERHADAP KOMPETENSI GURU PAK BERDASARKAN II KORINTUS 4:16-5:10 - Habel S.J. Rieuwpassa (KOLONI, 2023)
It is a reality that the rapid development of science and technology requires changes in policies in the field of education where changes and reforms in improving the quality of education have an impact on PAK teachers to change paradigms both from technical, teacher, philosophical, and psychological aspects, besides teachers also faced with the dynamics of the background of life that greatly affects the competence of PAK teachers in teaching and educating. A successful PAK teacher is a teacher who can realize competence in his performance so that the teacher is called a professional teacher. Because of the importance of PAK teacher competence, research on the Influence of Teacher Background on PAK Teacher Competence in Sorong City and District based on II Corinthians 4:16-5:10 becomes important for a more in-depth study. This study aims to determine the tendency of PAK teacher competence in Sorong City and District based on II Corinthians 4:16-5:10, the dominant indicator that manifests the tendency of PAK teacher competence in Sorong City and District based on II Corinthians 4:16-5:10, Background category The background of the dominant teacher manifests the tendency of PAK teacher competence in the City and District of Sorong based on II Corinthians 4:16-5:10. The research method used is an explanatory survey. The results obtained in this research are that they tend to be quite competent, lack enthusiasm in work, sometimes give themselves to be renewed, lack competency motivation. Keywords: Competency of PAK teachers, according to II Corinthians 4:16-5:10, Exploratory Survey Method